Double-blind randomised controlled trial of percutaneous tibial nerve stimulation versus sham electrical stimulation in the treatment of faecal incontinence : CONtrol of Faecal Incontinence using Distal NeuromodulaTion (the CONFIDeNT trial) /: CONtrol of Faecal Incontinence using Distal NeuromodulaTion (the CONFIDeNT trial). (September 2015) - Horrocks, Emma J
No abstract available